Cytotoxic and biological effects of bulk fill composites on rat cortical neuron cells - Kamalak, Hakan; Kamalak, Aliye; Taghizadehghalehjoughi, Ali; Hacimuftuoglu, Ahmet; Nalci, Kemal Alp (Springer, 2018)
The aim of this study was to investigate potential cellular responses and biological effects of new generation dental composites on cortical neuron cells in two different exposure times. The study group included five different bulk-fill flow able composites; Surefil SDR Flow, X-tra Base Flow, Venus Bulk Flow, Filtek Bulk Flow and Tetric-Evo Flow. They were filled in Teflon molds (Height: 4mm, Width: 6mm) and irradiated for 20s. Cortical neuron cells were inoculated into 24-well plates. After 80% of the wells were coated, the 3 mu m membrane was inserted and dental filling materials were added. The experiment was continued for 24 and 72h. Cell viability measured by MTT assay test, total antioxidant and total oxidant status were examined using real assay diagnostic kits. The patterns of cell death (apoptosis) were analyzed using annexin V-FITC staining with flow cytometry. B-defensins were quantitatively assessed by RT-PCR. IL-6, IL-8 and IL-10 cytokines were measured from the supernatants. All composites significantly affected analyses parameters during the exposure durations. Our data provide evidence that all dental materials tested are cytotoxic in acute phase and these effects are induced cellular death after different exposure periods. Significant cytotoxicity was detected in TE, XB, SS, FBF and VBF groups at 24 and 72h, respectively.
Keywords: Apoptosis; Cell viability; Cytotoxicity; Total antioxidant capacity; Total oxidant status